What's in It for the Historian of Science? Reflections on the Value of Philosophy of Science for History of Science. Issue 1 (2nd January 2017) - Arabatzis, Theodore
ABSTRACT: In this article, I explore the value of philosophy of science for history of science. I start by introducing a distinction between two ways of integrating history and philosophy of science: historical philosophy of science (HPS) and philosophical history of science (PHS). I then offer a critical discussion of Imre Lakatos's project to bring philosophy of science to bear on historical interpretation. I point out certain flaws in Lakatos's project, which I consider indicative of what went wrong with PHS in the past. Finally, I put forward my own attempt to bring out the historiographical potential of philosophy of science. Starting from Norwood Russell Hanson's insight that historical studies of science involve metascientific concepts, I argue that philosophical reflection on those concepts can be (and, indeed, has been) historiographically fruitful. I focus on four issues (epistemic values, experimentation, scientific discovery and conceptual change) and discuss their significance and utility for historiographical practice.